Anatomic Anterior Cruciate Ligament Reconstruction - A Prospective Evaluation Using Three-Dimensional Magnetic Resonance Imaging. Issue 7 (21st July 2017) - Hart, Adam; Sivakumaran, Thiru; Burman, Mark; Powell, Thomas; Martineau, Paul A.
Objectives: The recent emphasis on anatomic reconstruction of the anterior cruciate ligament (ACL) is well supported by clinical and biomechanical research. Unfortunately, the location of the native femoral footprint can be difficult or even impossible to see at the time of surgery. Most surgeons therefore rely on anatomic landmarks, custom drill guides, or general rules-of-thumb to guide femoral tunnel placement; however, the accuracy of these techniques to reconstruct each patient's native anatomy is poorly understood. The objective of this study was to use a previously described isotropic magnetic resonance sequence (3D MRI) to image patients with torn ACLs before and after reconstruction and thereby assess the accuracy of graft position on the femoral condyle in comparison to each patient's native ACL footprint. Methods: Forty-one patients with unilateral ACL tears were prospectively recruited into our study. Each patient underwent a 3D MRI of both the injured and uninjured knees before surgery. The contralateral (uninjured) knee scan was used to define the patient's native footprint. Patients then underwent ACL reconstruction with hamstring autograft by one of four experienced fellowship-trained sports orthopedic surgeons. The injured knee was reimaged after surgery. The location and percent overlap of the reconstructed femoral footprint was compared to the patient's native footprint. Results: The center of the native ACL femoral footprint was a mean of 16.4 +/- 4.6 mm distal and 5.3 +/- 2.9 mm anterior to the apex of the deep cartilage. The position of the reconstructed graft was significantly different, with mean distance of 10.4 +/- 2.7 mm distal (P < 0.0001) and 7.7 +/- 3.1 mm anterior (P = 0.001). The mean distance between the center of the graft and the center of the native ACL femoral footprint (error distance) was 5.7 +/- 3.6 mm. Comparing error distances amongst the four surgeons demonstrated no significant difference using the Kruskal-Wallis one-way ANOVA (P = 0.78). On average, 21% of the graft was within the native ACL femoral footprint. Of the 41 patients, 16 (39%) had the graft placed entirely outside the native ACL footprint. Conclusion: Despite contemporary techniques and a concerted effort to perform anatomic ACL reconstructions by four experienced sports orthopedic surgeons, the position of the femoral footprint was significantly different between the native and reconstructed ligaments. Furthermore, each of the four surgeons uses a different technique but all had comparable errors in their tunnel placements. In order to achieve a truly anatomic reconstruction, surgeons may consider using a pre-operative 3D MRI, which enables excellent visualization of the ACL's native anatomy and could potentially be used as a roadmap to guide anatomic tunnel placement.